Experimental investigation into rock burst proneness of rock materials considering strain rate and size effect - Li, Xiaobin; Wang, Haoteng; Zhao, Ying; Xue, Haifang; Li, Lingyun (Frontiers in Earth Science, 2023)
In the field of deep rock engineering, assessing the potential for rock bursts is crucial for safety purposes. In this study, a new indicator, the post-peak dissipated energy index, has been proposed to evaluate the rock burst proneness of rock materials, while taking into account the strain rate and size effect. Limestone and slate samples with various L/D ratios (ranging from 0.3 to 1.5) were subjected to conventional compression tests at four different strain rates (0.005, 0.01, 0.5, 1.0 s-1) to investigate rock burst proneness. Based on the rock failure characteristics, the actual rock burst proneness was classified into three categories (no risk, low risk, and high risk), and a new criterion was established using the post-peak dissipated energy index (the ratio of elastic energy to total dissipated energy). The impact of the strain rate and L/D ratio on rock burst proneness was then analyzed based on this new criterion. The results demonstrate that a strong hardening effect caused by increased strain rates induces a staged growth of rock burst proneness, while the rock burst proneness ratio decreases non-linearly with an increasing L/D. The accuracy of the proposed criterion was validated by comparing it to existing criteria, indicating that the energy-based index ensures a reliable evaluation of the rock burst proneness of rock materials.